Analisis Kelayakan Investasi Perkebunan Rambutan di Desa Jungkal Kecamatan Lampihong Kabupaten Balangan - Miranda Romaully Br. Sitanggang; Norhalimah Norhalimah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2014)
This study aims to determine the feasibility of rambutan plantation investment in Jungkal Village, Lampihong Subdistrict, Balangan Regency, seen from non-financial aspects, namely market aspects, technical aspects, management aspects, and financial aspects. The study was conducted in Jungkal Village, Lampihong District. The research method used was the census method where as many as 20 rambutan garden business owners were made respondents. Data collection was conducted from May - August 2014. Analysis of financial aspects used investment criteria consisting of Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B / C), and payback period. The results of research obtained from non-financial aspects show that the investment in rambutan plantation is feasible, it is shown that the market potential is quite high, the location of the plantation business that supports the success of the business, and the work plan in its management can be done by taking into account existing conditions. From the financial aspects of the rambutan plantation business investment in Jungkal Village, it is feasible to show the Net Present Vlue (NPV) of Rp134,646,379, - the value of the Internal Rate of Return (IRR) is greater than the discount rate of 30.01%. Net B / C is 4.50, and the payback period is 8 years 11 months 26 days, this shows that financially the investment in rambutan plantation is feasible.